THE RESOLUTION OF THE IRRESOLVABLE: THE ART AND PHILOSOPHY OF THE «ETERNAL» CONTRADICTIONS - Galina Ya. Verbitskaya; Sergei N. Semenov (Russian State Vocational Pedagogical University, 2016)
The aim of the work described in the article is to consider theproblem of philosophical understanding of the art of conflict as a model of dialectical contradictions; to justify prefigures the role of art in relation to theoretical knowledge through a comparison with the individual creative act, which gives the idea of a solution in a figurative and symbolic form; to consider «substantial» artistic conflicts in the drama as a manifestation of antinomic contradictions; to show the resolution of the data «eternal» contradictions in a particular situation by shifting to a qualitatively different semantic level of their perception on the example of catharsis in a new, modern drama, and to emphasize the role of art in education, in the understanding and assimilation of educational material, to learn the profession.Methods. Solution of the work purpose is carried out by analyzing dramatic works using the method of «slow reading» by D. S. Likhachev, and the technology of didactic design by V. E. Steinberg.Results. The more than twenty years experience of practice teaching of theatre history and drama theory, theatre criticism at the theatre department (the Ufa State Academy of Arts named by Zagir Ismagilov) for students mastering at theatre critics and directors courses. Developed and tested teaching method to the analysis of drama. The method of training in the analysis of the drama is developed and approved. Features of specifics formation of the concepts «conflict» and «contradiction» in the context of philosophy and art are considered. The main content of the specified concepts, their fundamental difference and a dialectic ratio is disclosed, and their role in the course of knowledge and training is emphasized. The general model of interaction of a contradiction and the conflict is developed.Practical significance. The article can be interesting and useful to teachers of creative and humanitarian universities, as well as directors, playwrights and theater critics.